Characterstic And Inhibitory Activity Of Green And Red Beans Yoghurt Enriched With Honey Against Methicillin-Resistant Staphylococcus Aureus - Sela Mustika Sari; Arista Wahyu Ningsih; Farida Anwaril; Iif Hanifa Nurrosyidah (Berkala Ilmiah Kimia Farmasi, 2021)
Currently probiotics are widely developed because of their health benefits such as helping to maintain a healthy digestive tract. One of the probiotic fermented products is yogurt. Yogurt on the market is made from cow's milk, so it cannot be consumed by people who are allergic to cow's milk or lactose intolerant. The purpose of this study was to develop a yogurt formulation based on vegetable juice, namely mung bean and kidney bean juice. The characterization of mung bean and kidney bean juice yoghurt was carried out by of organoleptic observation, fat content test, protein content test, ash content test, acidity test, total plate number (ALT) test and antibacterial activity test against Methicilli-resistant Staphylococcus Aureus (MRSA) by the agar diffusion method using wells. The results of the product characterization based on mung bean juice and kidney bean enriched with honey meet the quality characteristics of SNI yogurt (2981:2009), including the appearance of thick-solid liquid, normal/typical odor, sour/typical taste, homogeneous consistency. Fat content test, the average F1 was 1.063% (SD = 0.0026), F2 1.025% (SD = 0.0031), F3 1.035 (SD = 0.0033); the average protein content of F1 12.51% (SD=0.01244), F2 11.90% (SD=0.0120), F3 12.08% (SD=0.02); mean ash content of F1 0.36% (SD= 0.0410), F2 0.52% (0.0821), F3 0.39% (SD 0.0294); the average acid content of F1 0.858% (SD= 0.0084), F2 0.873% (0.0199), F3 0.936 (SD= 0.0336); the number of starter bacteria on average was 5.4 x 109 CFU/mL (SD= 0.927), F2 4.3 x 109 CFU/mL, F3 5.6 x 109 CFU/mL. The antibacterial activity of the yogurt was included the strong category, the inhibition zone produced more than 20 mm. The average inhibition zone by F1 was 21.667 mm (SD= 0.489), F2 22.667 mm (SD= 0.489), F3 22 mm (0.4).